Paciente femenino de 65 años de edad con hipertensión y obesidad grado 2 - Flores Leturne, Nathaly Jasmin (2019)
This case is about a 65-year-old female patient belonging to San Juan parish, was diagnosed 2 years ago with arterial hypertension, goes to the clinic because lately she has felt bad, has headaches and very frequent muscle aches, in the background pathological his parents died of hypertension and diabetes, a nutritional evaluation is performed which presented a BMI of grade 2 obesity with severe cardiovascular risk; In addition, biochemical tests were performed, which ruled out the possibility of diabetes but presented hypercholesterolemia and hypertriglyceridemia since their diet was very high in fat and simple carbohydrates, in addition to not liking salads and preferring to drink fruit juice and not eat them whole, on physical examination reveals an excess of weight, difficulty walking. A meal plan is made depending on the patient's caloric needs, the diet will be hypocaloric, high-fiber hypo-fat and hyposodic 2.5 to 4 g per day of sodium that will be divided into 4 meals a day, that is, a snack and its three main Daily meals (breakfast, lunch, snack) in their respective corresponding schedule this diet will be based on the most frequent consumption of vegetables, fruits, complex carbohydrates, in addition to the diet an important factor such as physical activity is included, which will be walking for 30 m a day, at least three times a week since this activity will improve your cardiovascular function. By monitoring and monitoring, improvements are observed in the patient, his biochemical tests are improving by lowering cholesterol and triglycerides.